LIS1 and DCX: Implications for Brain Development and Human Disease in Relation to Microtubules - Orly Reiner (Scientifica)
Proper lamination of the cerebral cortex requires the orchestrated motility of neurons from their place of birth to their final destination. Improper neuronal migration may result in a wide range of diseases, including brain malformations, such as lissencephaly, mental retardation, schizophrenia, and autism. Ours and other studies have implicated that microtubules and microtubule-associated proteins play an important role in the regulation of neuronal polarization and neuronal migration. Here, we will review normal processes of brain development and neuronal migration, describe neuronal migration diseases, and will focus on the microtubule-associated functions of LIS1 and DCX, which participate in the regulation of neuronal migration and are involved in the human developmental brain disease, lissencephaly.